An Efficacy and Feasibility Analysis of Chinese Patent Medicine Combined With Letrozole in the Treatment of Women With Ovulation Disorders: A Network Meta-Analysis - Zhu, Jing-Yan; Liu, Jian; Cao, Xiao-Jing; Wang, Xiao-Yun (Frontiers in Pharmacology, 2021)
Objective: To compare the efficacy of various listed Chinese patent medicines combined with letrozole in the treatment of ovulation disorders using network meta-analysis (NMA). Methods: We conducted a systematic literature search in PubMed, Cochrane Central Register of Controlled Trials, Embase, Chinese Biomedical Literature, China National Knowledge Infrastructure, Wanfang, and VIP Information databases up to June 2020. Randomized controlled trials reporting Chinese patent medicine combined with letrozole for ovulation disorders were included. The Stata 13 and WinBUGS1.43 software were used for data analysis. Results: A total of 24 randomized controlled trials were included, involving 2,318 patients. The results showed that when compared with patients using only letrozole, the ovulation rate was higher in patients using letrozole combined with Kuntai capsules, Fuke Zaizao capsules, Fufang Xuanju capsules, or Dingkun Dan, and Fufan Xuanju capsules showed the greatest improvement; the pregnancy rate was higher in patients using letrozole combined with Kuntai capsules, Fuke Zaizao capsules, or Dingkun Dan; and the endometrial thickness on the day of follicular maturity was greater in patients using letrozole combined with Kuntai capsules, Fuke Zaizao capsules, Fufang Xuanju capsules, Bailing capsules, or Dingkun Dan. In terms of the sequencing of NMA results, Fufang Xuanju capsules combined with letrozole gave the best results in improving the ovulation rate and increasing the endometrial thickness, while Dingkun Dan combined with letrozole achieved the best results for improving the pregnancy rate. Conclusion: Letrozole combined with Chinese patent medicine is more effective than letrozole alone in the treatment of ovulation disorders. Fufang Xuanju capsules is good at improving the ovulation rate and increasing the endometrial thickness. Dingkun Dan is good at improving the pregnancy rate. The appropriate choice of treatment should be made according to the actual clinical situation. This study is registered with the International Prospective Register of Systematic Reviews (CRD42020200603).